2021
DOI: 10.18632/aging.203075
|View full text |Cite
|
Sign up to set email alerts
|

Risk of arterial stiffness according to metabolically healthy obese phenotype: a combined cross-sectional and longitudinal study in kailuan cohort

Abstract: BackgroundTo investigate the risk of incident arterial stiffness according to metabolically healthy obese (MHO) phenotype in Chinese population. Materials and methodsThe Kailuan study is an ongoing prospective cohort study, 37,180 participants with at least one-time measurement of branchial-ankle pulse wave velocity (baPWV) were included in the cross-sectional analysis, and 16,236 participants with repeated measurement of baPWV during the follow-ups were included in the longitudinal study from March 1, 2010… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 27 publications
1
3
0
Order By: Relevance
“…In addition, the study population was smaller than the present study [ 15 ]. Our study, which was conducted among a relatively high number of Chinese adults and adopted a reasonable cutoff value of elevated baPWV, showed that participants with MUNO had a significantly higher baPWV and odds ratio of elevated baPWV than participants with MHNO and MHO, consistent with previous studies [ 22 , 23 ]. In addition, the Framingham risk score was used to assess the 10-year CVD risk in MUNO individuals.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In addition, the study population was smaller than the present study [ 15 ]. Our study, which was conducted among a relatively high number of Chinese adults and adopted a reasonable cutoff value of elevated baPWV, showed that participants with MUNO had a significantly higher baPWV and odds ratio of elevated baPWV than participants with MHNO and MHO, consistent with previous studies [ 22 , 23 ]. In addition, the Framingham risk score was used to assess the 10-year CVD risk in MUNO individuals.…”
Section: Discussionsupporting
confidence: 91%
“…Because there is no definite cutoff value for elevated baPWV and the cutoff value is different between male and female populations, it is reasonable to define the sex-specific upper quartile of baPWV of the study population as the cutoff value of elevated baPWV. To the best of our knowledge, three studies investigated the relationship between MUNO and baPWV in a Chinese population, but the cutoff value of elevated baPWV was robust in two of the three studies [ 22 , 23 ]. In addition, the study population was smaller than the present study [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Kailuan Study is a population-based prospective cohort study that includes current and retired employees of the Kailuan Group. 20 NHANES is a comprehensive U.S. public database that evaluates the health and nutritional statuses of American adults and children, serving as a resource for epidemiological and health-related research. Participants from both cohorts were asked to complete a detailed questionnaire including demographic and sociological information, as well as data on lifestyle habits and dietary intake.…”
Section: Methodsmentioning
confidence: 99%